EFEKTIVITAS PELAYANAN PROGRAM BINA KELUARGA REMAJA (BKR) DALAM MEWUJUDKAN KETENTRAMAN KELUARGA: (Studi Pada Kelurahan Bumi Jaya Kecamatan Anak Tuha Kabupaten Lampung Tengah) - Hasan, Noffandra Hasan; Handayani, Tuti (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2022)
Adolescence is a period of transition, namely the transition period from childhood to adulthood, which experiences the development of all aspects/functions to enter adolescence. Many programs are provided by the government in terms of improving and improving the quality of youth in Indonesia. This approach to the family is carried out through the development of the Youth Family Development group (BKR). Youth Family Development is an activity carried out by a group of families or parents to improve guidance, guidance, or even knowledge of adolescent growth and development in a good and directed manner in order to build a quality family. This research aims to determine the effectiveness of the Youth Family Development Program (BKR) in realizing family peace in Bumi Jaya Village, Kec. Son of God Kab. Central Lampung. And to find out the inhibiting and supporting factors of the effectiveness of the Youth Family Development Program (BKR) in realizing family peace in Bumi Jaya Village, Anak Tuha sub-district, Central Lampung district. In this research, the method used is a qualitative method. The result of this research is that the Youth Family Development (BKR) program in Realizing Family Peace in Bumi Jaya Village, Anak Tuha District, Central Lampung Regency has been effective. Seen and measured from various indicators ranging from optimizing goals, and systems perspective to. emphasis on human behavior in organizational structures. Then the next inhibiting factor is the lack of facilities and infrastructure to support the implementation of the Youth Family Development program in the Bumi Jaya Village, Central Lampung Regency, and also the members of the Family Planning Board who are considered to be lacking in real action Keywords: Effectiveness, Family, Teen